KETERAMPILAN MENULIS DENGAN MODEL PAKEM MELALUI TEKNIK ‘MENJADI WARTAWAN JUNIOR’ DI SEKOLAH DASAR - Cahyani, Isah; Hadianto D, Daris (Universitas Pendidikan Indonesia, 2019)
This research is motivated by the condition of students' writing abilities that are still low. One method that is considered appropriate is the PAKEM model by positioning students as junior journalists. The research method that I use is a quasi-experimental research method with a quantitative approach. The quantitative approach is used to obtain a picture of the ability of students to write reports on interviews through the technique of 'Becoming a Junior Reporter'. In addition, this study also uses a qualitative approach to describe the profile data of students' ability to write reports on the results of interviews through the technique of 'Becoming a Junior Journalist' before the learning approach to writing through the 'Becoming a Junior Journalist' technique is applied. The 'Become a Junior Journalist' technique is effective for improving students' ability to write reports based on an increase in the average pretest score of 57.47 to 78.50 on the average posttest score. Meanwhile, the final average value of the control class was 57.00 in the pretest and increased by 68.78 on the average posttest score. There was a difference in gain of 21.03 in the experimental group and 11.78 in the control group. This proves that writing ability can be improved with the PAKEM model through junior journalist techniques.